Successful Building Using Ecodesign - Gobin, Christophe; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The notion of ecodesign has now clearly become part of the building sector. It involves taking into consideration environmental issues that are indispensible in constructing our living environment. However, this method, which is industrial in origin, clearly shows that buildings are not the result of simply adding up technical rules. A much more demanding process underpins their development, one that engages all stakeholders in the industry and leads them towards using a new practice involving multi-criteria choices that are never unique. The object of this work is to review each of the stages in a building operation to illustrate the necessity of optimization and to observe the useful contribution that ecodesign and its tools can make. Ecodesign has been tackled from the professional point of view of those involved in construction work. In this perspective, the central tool is clearly that of the life cycle analysis (LCA) This book therefore describes the different steps of a project management cycle in accordance with a functional analysis. The product achievement is evaluated with the life cycle analysis which can be used as a measurement of its efficiency.
1 Ecodesign in the programming phase --1.1 Mobilizing those involved --1.2 Considered parameters --1.3 Obtained results --1.4 Transfer modalities --1.5 Overview diagram -- 2 Ecodesign in the design phase --2.1 Mobilizing the actors --2.2 Considered parameters --2.3 Obtained results --2.4 Transfer modalities --2.5 Overview diagram -- 3 Ecodesign in the production phase --3.1 Mobilizing the actors --3.2 Considered parameters --3.3 Obtained results --3.4 Transfer modalities --3.5 Overview diagram -- 4 Ecodesign in the operation phase --4.1 Mobilizing the actors --4.2 Operation phase optimisation --4.3 Rehabilitation --4.4 Experience feedback --4.5 Overview diagram -- Conclusion -- Annexes --Annex 1. LCA approach --Annex 2. Measuring an ecodesign project management
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Structural; construction; durable architecture; environmental science; green building; LCA; Life-cycle analysis; Structural engineering; Sustainable construction; Product life cycle; Electronic books